Catalytic nitriding of steel components operating in difficult conditions of hydro-abrasive wear (Texas Journal of Multidisciplinary Studies, 2022)
In the paper, the catalytic effect of previously deposited copper oxide film on nitriding process is described. Mechanisms of iron nitriding intensification are discussed: ammonia dissociation, nitrogen ions adsorption at metal surface, and nitrides formation acceleration. Microstructure of nitrided layers in Armcoiron and in high-chromium steel is examined. It was shown the increase of abrasive wear resistance of nitrided 20Cr13 steel.